The Effect of Coconut Powder on Asphalt Binder Performance under Laboratory Conditions - Rana Yousif; Sady Tayh; Abbas F. Jasim (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Bituminous concrete mixture is the most widely used structural layer in flexible pavements. The surface layer of the paving is exposed to repeated loads in addition to changes in temperature, especially during the summer, when the temperature approaches the softness point of the asphalt binder, and therefore, it is subject to multiple types of failure, especially rutting. The properties of asphalt binder and asphalt mixtures can be improved by using various additives. Coconut shell powder, made from the dried husk of coconut fruit, is a popular addition in many industries. As a result of its high strength and stability, this waste material can be recycled into functional structural components such as composite material reinforcement. This study was conducted to evaluate the performance of coconut husk as very fine particles passing through sieve number 200 (0.075 mm) to modify the asphalt binder. The modifier was added at rates of (0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10) by the weight of asphalt binder. Two asphalt binder types, 80/100 and 40/50 penetration grade, were used in this study. All asphalt samples were tested for penetration, softening point, rotational viscosity, and dynamic shear rheology. The results showed that the modified samples had better physical and rheological properties compared to the base asphalt binders. However, (7-8%) replacement of coconut husk powder, regardless of the base asphalt binder, yielded the best performance among the modified binders. In conclusion, coconut powder has significant potential as a road-building material due to its impact on the viability of the road construction sector